2017
DOI: 10.3389/fpsyt.2017.00185
|View full text |Cite
|
Sign up to set email alerts
|

An Update Overview on Brain Imaging Studies of Internet Gaming Disorder

Abstract: There are a growing number of studies on structural and functional brain mechanisms underlying Internet gaming disorder (IGD). Recent functional magnetic resonance imaging studies showed that IGD adolescents and adults had reduced gray matter volume in regions associated with attention motor coordination executive function and perception. Adolescents with IGD showed lower white matter (WM) integrity measures in several brain regions that are involved in decision-making, behavioral inhibition, and emotional reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 102 publications
3
62
0
Order By: Relevance
“…Resting-state functional connectivity (rsFC), identifying abnormal networks of brain areas exhibiting synchronous blood oxygen level-dependent (BOLD) fluctuations, was extensively used in psychiatric research, including substance addiction [19] and IA [20]. Using rsFC analysis, previous studies have revealed the abnormal functional interaction within the VS-frontal circuit in IA [12] and demonstrated the normalization of the ventral striatal network after a virtual reality treatment in adolescents with IA [21].…”
Section: Introductionmentioning
confidence: 99%
“…Resting-state functional connectivity (rsFC), identifying abnormal networks of brain areas exhibiting synchronous blood oxygen level-dependent (BOLD) fluctuations, was extensively used in psychiatric research, including substance addiction [19] and IA [20]. Using rsFC analysis, previous studies have revealed the abnormal functional interaction within the VS-frontal circuit in IA [12] and demonstrated the normalization of the ventral striatal network after a virtual reality treatment in adolescents with IA [21].…”
Section: Introductionmentioning
confidence: 99%
“…Among men, 79.3% (n=69) reported being heterosexual, 6.9% (n=6) homosexual, and 13.8% (n=12) bisexual, and among women, 75.9% (n= 44) reported being heterosexual, 8.6% (n=5) homosexual, and 15.5% (n=9) bisexual.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to those who engage in other Internet-related behaviors such as gaming [7][8][9], however, some cybersex users may develop excessive patterns of use with possible negative consequences [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Precuneus activation creates visual, imaginary, attention, and memory processes, which later are followed by happy memory coding by the parahippocampal area. [15][16][17][18]…”
Section: Emotional and Memory Processesmentioning
confidence: 99%
“…After cessation of excessive internet usage, activity in the right DLPFC and left parahippocampal gyrus appeared lower than before. 15,16 Internet addiction creates a serious problem for the mental and physical development of teenagers, therefore an accurate diagnostic tool is needed so that treatment can be administered immediately, because, as with most behavioral problems, the earlier the condition can be identified, the easier it is to correct. Moreover, it is also important to distinguish between normal child or adolescent behavior from which is pathologic and requires therapeutic intervention.…”
Section: Craving and Conflict Processesmentioning
confidence: 99%